Optimization of the Risk Functional to Control the Composition and Structure of a Heterogenous Grouping of Detection Sensors in Three-Dimensional Space - Dyukov, V. A.; Kazantsev, A. M.; Makushev, I. Yu; Putilin, M. S.; Timoshenko, A. V. (Journal of computer & systems sciences international, 2023)
The steady growth in the scale and dynamics of the use of aerial weapons in the course of various conflicts necessitates the formulation and solution of the problems of building realistic systems to detect them. It should be noted that the priorities in the development of detection sensors is changing from solving problems to improve their characteristics to optimization and adaptability in controlling them. As an object, a heterogeneous grouping of sensors, which solves the problem of detecting a moving airborne object, is considered. The subject is the methodology for constructing control models for heterogeneous detection sensors. Based on the analysis of the antagonistic interaction of a heterogeneous grouping and airborne objects, as well as the processes of their functioning, a geometric approach to solve the problem of detecting a moving object (MO) is proposed, which uses an adapted and improved risk functional as one of the possible indicators for the further synthesis of the control algorithms. The practical effectiveness of the application of this functionality is substantiated and compared with other performance indicators through simulation modeling.